Evading and embracing normality: estrangement and ambivalence in the accounts of methamphetamine consumers - Duff, Cameron; Moore, David (Routledge, 2015)
© 2014 Taylor & Francis. While much has been made of the governmentality evinced in drug policy, its effects on people who use drugs have received less attention. Scholars who have investigated these effects commonly focus on the views and experiences of individuals receiving treatment for their drug use, often reporting an explicit desire among individuals in treatment for a return to a normal, healthy life. Many authors trace this desire to the normalisation inherent in drug policy, and the governmentality involved in the delivery of drug treatment more directly. This article adds to these discussions by shifting focus from the experience of individuals in treatment to those out of treatment settings. In so doing, we aim to develop a more nuanced understanding of how heavy drug users negotiate power, governmentality and the modulations of health and illness in the course of everyday life. We ground our discussion in qualitative research conducted in Melbourne, Australia, with 31 current methamphetamine consumers. We argue that regular methamphetamine consumption involves a complex and ambivalent relationship with the ideas of health and normal life, imposing as well as reflecting a form of estrangement between its consumers and mainstream (or normal) society. This ambivalence has important implications for the delivery of health and social services among methamphetamine consumers, insofar as the restoration of normal health and the reintegration of former drug users into mainstream society are typical health service goals. We address some of these policy implications by way of conclusion.